Pengaruh Efikasi Diri, Harga Diri, dan Lokus Kendali Internal Terhadap Kinerja Pengelola Koperasi Simpan Pinjam di Kecamatan Bangkalan pada Masa Pandemi Covid-19 - Bhiatul Ayu Fitriya; Mudji Kuswinarno (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The number of cooperatives in Bangkalan Regency continues to decline because there are many cooperatives that do not operate indicating that the cooperative management is not doing well, one of which is a cooperative with a savings and loan business in Bangkalan District. The performance problems of saving and loan cooperative managers occur because of the influence of personality factors such as self-efficacy, self-esteem, and internal locus of control. This study uses quantitative methods using multiple regression analysis and the sampling technique is simple random sampling. The total population was 65 people and the number of samples used was 56 people. Partially and simultaneously self-efficacy, self-esteem, and internal locus of control have a positive and significant effect on the performance of cooperative managers and self-efficacy is a dominant variable with the highest beta.